2017
DOI: 10.1038/nmat4886
|View full text |Cite
|
Sign up to set email alerts
|

Electric field control of deterministic current-induced magnetization switching in a hybrid ferromagnetic/ferroelectric structure

Abstract: All-electrical and programmable manipulations of ferromagnetic bits are highly pursued for the aim of high integration and low energy consumption in modern information technology. Methods based on the spin-orbit torque switching in heavy metal/ferromagnet structures have been proposed with magnetic field, and are heading toward deterministic switching without external magnetic field. Here we demonstrate that an in-plane effective magnetic field can be induced by an electric field without breaking the symmetry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
198
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 434 publications
(217 citation statements)
references
References 30 publications
2
198
2
3
Order By: Relevance
“…Cai et al . reported that the polarization of PMN‐PT ferroelectric substrates can be used to control the spin–orbit torque in the absence of an external magnetic field in a PMN‐PT/Pt/CoNiCo/Pt system, as shown in Figure a.…”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al . reported that the polarization of PMN‐PT ferroelectric substrates can be used to control the spin–orbit torque in the absence of an external magnetic field in a PMN‐PT/Pt/CoNiCo/Pt system, as shown in Figure a.…”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 99%
“…Magnetization switching induced by the polarization of PMN‐PT substrate. a) The structure of the device; b,c) the deterministic magnetization switching after applying 500 and −500 V. Reproduced with permission . Copyright 2017, Nature Publishing Group.…”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 99%
“…The other is that an additional symmetry-breaking field is required for the deterministic switching of perpendicular magnetization. As a result, much effort has been expended in realizing field-free SOT switching at a low current [17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ferromagnetic SRO is widely used as an electrode for thin films such as ferroelectrics [25]. Considering that magnetoelectric heterostructures consisting of ferromagnetic and ferroelectric elements have recently aroused great interest due to their promising applications [26][27][28], the presence of NM grain boundaries in the FM SRO layers is expected to significantly change the interfacial magnetoelectric coupling.…”
Section: Discussionmentioning
confidence: 99%